RESEARCH OF THE INERTIAL DEVIATION MEASUREMENT SYSTEM UAV CARGO FROM ZERO POINT - BOIKO, Juliy; SVACHII, Oleh (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Inertial measurement units (IMUs) can consist of one or more sensors that collect data designed to measure inertial motions in a specific frame of reference. Acceleration, rotational speed are examples of data that can be obtained from the sensors contained in the IMU. IMUs can be found in a variety of smart devices, medical rehabilitation, general robotics, UAV control and navigation enhancement systems, sports devices, and virtual reality systems. Some engineering solutions and displacement sensors have a number of limitations, such as systems that do not have a clear initial reference point. In such systems, it is difficult to track deviations from the starting point. However, the acceleration of a moving object is usually easy to measure, so the given deflection of the object can easily be obtained using the integral of the acceleration. To solve such problems, a distance measurement system based on a microelectromechanical system (MEMS) accelerometer has been developed. The hardware structure of the system includes a data measurement module and integrated data collection and data processing modules. Due to the physical properties of the sensor, such a system can be used in a small space, with large overloads and other adverse conditions. This article describes a system calibration method and proposes a deviation tracking algorithm based on acceleration integration. Fixed output error caused by sensor mounting position is analyzed. The analysis shows that if this factor is not taken into account, the error will lead to a serious error. The experiment of measurement of the deviation from the zero point is carried out on a horizontal, flat surface, and the calculation results show that the average accuracy of the deviation measurement of this system can reach 99.05%. The results of the experiment indicate the feasibility of the system in the conditions of short-term free fall and the validity of the data processing algorithm. The accuracy of the distance measurement system can meet most engineering needs.